The Power of Words: An Empirical Analysis of the Communicative Value of Extended Auditor Reports - Seebeck, Andreas; Kaya, Devrimi (European Accounting Review, 2023)
We examine the communicative value of extended auditor reports in the United Kingdom (UK), where ISA 700 (UK and Ireland) requires auditors to disclose the risks of material misstatement that had the greatest effect on the audit–key audit matters (KAM). By using methods from computational linguistics, we find that different proxies for communicative value (i.e., readability, evaluative content, visual aids, and specificity) improve in post-ISA 700 periods. Cross-sectional tests show that the improvement differs across audit firms and audit clients as well as KAM disclosure characteristics. Finally, broadly consistent with concurrent studies, we find no evidence that several proxies for communicative value are informative to investors. However, we find initial evidence that a more specific description of KAM is significantly and positively associated with capital market reactions, suggesting that investors value precise information. Overall, this study directly responds to the call for more research on how KAM are worded.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Communicative value; Critical audit matters (CAM); Extended auditor reporting; Key audit matters (KAM); Specificity; Textual analysis